Victoria Skibsted Nielsen - A thesis submitted in partial fulfilment of the requirements of the degree of Doctor of Clinical Psychology (DClinPsych) - Nielsen, VS (2022)
Critical Review of the Literature (CRL) Abstract: An exploration of betrayal within mental contamination in OCD: a mixed-methods systematic narrative review